2018
DOI: 10.1108/pr-08-2016-0209
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial effects of proactivity

Abstract: Purpose Although proactivity is thought to have positive effects in the workplace, researchers still need to learn more about the contingent aspects of these effects. Proactivity, a challenging form of promotive behavior that is generally desired by organizations, can lead to unexpected consequences such as role overload, job strain, and conflict with coworkers, which may undermine future proactivity. The purpose of this paper is to examine the impact of proactive behavior on job satisfaction, affective commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Another cross-sectional study with teachers showed that proactive behaviour was positively related to affective well-being outcomes, including job satisfaction and commitment (Ghitulescu, 2018). In addition, collaborative behaviour buffered the negative link of proactive behaviour with experienced conflict.…”
Section: Beneficial Effects Of Proactive Behaviourmentioning
confidence: 97%
“…Another cross-sectional study with teachers showed that proactive behaviour was positively related to affective well-being outcomes, including job satisfaction and commitment (Ghitulescu, 2018). In addition, collaborative behaviour buffered the negative link of proactive behaviour with experienced conflict.…”
Section: Beneficial Effects Of Proactive Behaviourmentioning
confidence: 97%
“…Finally, individual initiative means that individuals voluntarily and creatively engage in workrelated behaviors that exceed the requirements (Podsakoff et al, 2000). According to Ghitulescu (2018), work-related problems that require flexibility and adaptation can trigger individual initiative behavior. In construction projects, such behaviors specifically includes putting forward constructive opinions, adopting advanced management and technical methods, pointing out potential improvements, voluntarily undertaking tasks, etc.…”
Section: Empowering Leadership and Individual Outcomesmentioning
confidence: 99%
“…On the one hand, the positive association between proactive behavior and well-being outcomes has been found in several empirical studies. In addition to crosssectional evidence (e.g., Claes & Van Loo, 2011;Ghitulescu, 2018;Greenglass & Fiksenbaum, 2009;Wang & Li, 2015), researchers have started to employ daily-diary (e.g., Starzyk et al, 2018;Weigelt et al, 2018) and experimental designs (e.g., Wolsink et al, 2019) to study relationships between proactivity and well-being. For example, Starzyk et al (2018) conducted a daily-diary study, which found that problem-focused voice (i.e., a form of proactive behavior) during meetings was associated with higher positive affect at the end of the next working day.…”
Section: Effects Of Proactive Behavior On Occupational Well-beingmentioning
confidence: 99%